2014
DOI: 10.1017/s0033291714000518
|View full text |Cite
|
Sign up to set email alerts
|

Brain grey matter abnormalities in medication-free patients with major depressive disorder: a meta-analysis

Abstract: Background. Because cerebral morphological abnormalities in major depressive disorder (MDD) may be modulated by antidepressant treatment, inclusion of medicated patients may have biased previous meta-analyses of voxel-based morphometry (VBM) studies. A meta-analysis of VBM studies on medication-free MDD patients should be able to distinguish the morphological features of the disease itself from those of treatment.Method. A systematic search was conducted for the relevant studies. Effect-size signed differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
119
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(129 citation statements)
references
References 61 publications
8
119
1
1
Order By: Relevance
“…Several meta-analyses considering automated and userindependent structural data analysis approaches, such as voxel-based morphometry (VBM), have consistently demonstrated gray matter volume (GMV) reductions in anterior cingulate cortex (ACC), dorsolateral prefrontal cortex (DLPFC), and hippocampus in patients with MDD (Bora et al 2012, Du et al 2012, Lai 2013, Zhao et al 2014). These investigations have reinforced existing neuroanatomical models of affective disorder (Price and Drevets 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Several meta-analyses considering automated and userindependent structural data analysis approaches, such as voxel-based morphometry (VBM), have consistently demonstrated gray matter volume (GMV) reductions in anterior cingulate cortex (ACC), dorsolateral prefrontal cortex (DLPFC), and hippocampus in patients with MDD (Bora et al 2012, Du et al 2012, Lai 2013, Zhao et al 2014). These investigations have reinforced existing neuroanatomical models of affective disorder (Price and Drevets 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…While only few studies have explicitly addressed the effects of antidepressant treatment on GMV (Hamilton et al 2008, Smith et al 2013, Kong et al 2014, Zhao et al 2014, preliminary evidence suggests that selective serotonin reuptake inhibitor treatment may be associated with GMV increase in DLPFC (Smith et al 2013), ACC (Zhao et al 2014, Willard et al 2015 and/or amygdala (Hamilton et al 2008). In an attempt to distinguish morphological features of the disease itself from those of treatment, were here included subgroups of medicated and non-medicated patients with acute MDD, as well as a subgroup of remitted patients on maintenance therapy.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression is associated with atrophy and loss of neurons in limbic and cortical brain areas, which could contribute to the symptoms of depression [23]. Moreover, magnetic resonance imaging shows smaller hippocampal volume in depressed patients besides changes in other limbic areas [36,37]. We have proposed that chronic hyperglycemia, imposed by the diabetic condition, is a more reliable animal model to mimic human depression since, unlike from acute stressors, it affects brain plasticity and function over time [2,9,32].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, structural alterations in the ACC may be associated with the affective and cognitive dysfunctions in MDD. Some studies have focused on the early morphological changes in first-episode, medication-naive MDD patients [28][29][30]. A recent study in untreated, firstepisode, mid-life MDD patients showed a modestly negative correlation between cortical thickness in the rostral middle frontal cortex and depression severity based on the Hamilton Depression Rating Scale (HDRS) [31] (Fig.…”
Section: Mr Imaging Of Brain Morphology and Structurementioning
confidence: 99%